2013
DOI: 10.2478/v10288-012-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Survey of recreational use of The Las Kabacki forest nature reserve in Warsaw (Poland)

Abstract: In an urban landscape, green areas are the key leisure facility for inhabitants, providing them with opportunities to relax and observe wildlife. With relevant infrastructure in place, these areas facilitate sport activities, ensuring mental and physical well-being. Sometimes they are a source of inspiration for artists. Without contact with nature, people become depressed, and the quality of their life deteriorates (Oleksiejuk, Jankowska 2009, Bożętka 2008, Chmielewski et al. 1996, Piątkowska 1983). This opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In Poland and other European countries, such workings are often transformed into forests or water bodies which then serve recreation, teaching, natural or technical purposes [20][21][22][23]. The criteria for selecting the right approaches to reclamation for any single area are determined by economic, formal and legal, geological and engineering, cultural and environmental factors [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland and other European countries, such workings are often transformed into forests or water bodies which then serve recreation, teaching, natural or technical purposes [20][21][22][23]. The criteria for selecting the right approaches to reclamation for any single area are determined by economic, formal and legal, geological and engineering, cultural and environmental factors [24].…”
Section: Introductionmentioning
confidence: 99%
“…Issues related to the development of former mineral workings are considered in various aspects, including the possibility of transforming them into water bodies. These issues concern the general concept plan for the reclamation, the principles of water management and also the impact of earlier opencast mining on groundwater circulation and water quality [24,25]; such considerations guide the reclamation of degraded areas in various parts of Poland [27].…”
Section: Introductionmentioning
confidence: 99%
“…We interpreted the received answers with reference to age categories and city size. According to Malinowska and Szumacher [32], the gender category is not decisive in this kind of research. The results were analyzed mainly based on the percentage of indicated answers received in relation to the total number of respondents in each category.…”
Section: Questionnairementioning
confidence: 97%
“…According to a social survey, only sanitary and hygienic issues needed to be solved in order to prevent the devastation of the forest. Kabacki Forest was also surveyed by Malinowska and Szumacher [32], this time from diverse points of view: awareness of threats to the natural environment caused by recreational pressure; readiness to abandon the preferred forms of rest and recreation in order to increase the effectiveness of the protection of nature; the possibility of resolving conflicts between recreational use of the reserve and nature protection needs; natural values and their perception; and preferred forms of recreational behavior. The survey revealed that Kabacki Forest nature reserve is perceived primarily as a recreational area for residents of nearby neighborhoods.…”
Section: Urban Nature Reserves (Unr)-what Is Their Purpose In Cities?mentioning
confidence: 99%
See 1 more Smart Citation